2012
DOI: 10.1097/ta.0b013e31822c1c50
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous extraction of deeply-embedded radiopaque foreign bodies using a less-invasive technique under image guidance

Abstract: Percutaneous extraction of RFBs from deep soft tissue with the present technique is safe, effective, and minimally invasive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Previous studies have reported the removal of foreign bodies, including gun pellets (n = 223), metal splinters (n = 24), and needle fragments (n = 4) using an 18-gauge needle, tapered dilators, and grasping forceps under fluoroscopic guidance [1] . Additional studies have reported the removal of ballistic foreign bodies (n = 61) using ultrasound or fluoroscopy [2] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported the removal of foreign bodies, including gun pellets (n = 223), metal splinters (n = 24), and needle fragments (n = 4) using an 18-gauge needle, tapered dilators, and grasping forceps under fluoroscopic guidance [1] . Additional studies have reported the removal of ballistic foreign bodies (n = 61) using ultrasound or fluoroscopy [2] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports describe removal of foreign bodies using image guidance with serial tract dilation or blunt and sharp dissection techniques [1] , [2] . This report describes a novel technique utilizing balloon tract dilatation to facilitate the removal of retained radiopaque soft tissue foreign bodies under fluoroscopic guidance.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, imaging is required to identify the foreign body and establish its exact location before the removal attempt. Intraoperative US and fluoroscopy have been used to help in surgical removal (3,(9)(10)(11)(12)(13). However, the surgical removal of a foreign body is invasive and technically challenging, and it requires a relatively large cutaneous and sometimes fascial incision, with isolation of neurovascular structures.…”
Section: Introductionmentioning
confidence: 99%